2014
DOI: 10.3109/08923973.2014.956754
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and anti-proliferative effects of CBS3830 in arterialized vein grafts in rats

Abstract: CBS3830 significantly decreases inflammation and intimal hyperplasia in AVGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Multiple studies have demonstrated that inhibition of MAPK in animal vein graft models results in reduced neointimal hyperplasia (Zhao et al, 2014; Evans et al, 2015). The phosphatidylinositol 3-kinase-Akt (PI3K-Akt) pathway also modulates vein graft remodeling; PI3k-Akt activation promotes cell survival and protein synthesis by activation of downstream signals, including the mammalian target of rapamycin (mTOR) protein (Mitra et al, 2006).…”
Section: Membrane Signaling In Human Vascular Physiology and Pathophymentioning
confidence: 99%
“…Multiple studies have demonstrated that inhibition of MAPK in animal vein graft models results in reduced neointimal hyperplasia (Zhao et al, 2014; Evans et al, 2015). The phosphatidylinositol 3-kinase-Akt (PI3K-Akt) pathway also modulates vein graft remodeling; PI3k-Akt activation promotes cell survival and protein synthesis by activation of downstream signals, including the mammalian target of rapamycin (mTOR) protein (Mitra et al, 2006).…”
Section: Membrane Signaling In Human Vascular Physiology and Pathophymentioning
confidence: 99%
“…10 A disfunção, proliferação e migração destas células são estimuladas pela fosforilação de p38 proteínas quinases ativadas por mitógeno (p38 MAPKs), quinases reguladas por sinal extracelular (ERK), c-Jun e quinases N-terminais. 11 Estudos têm demonstrado que a inibição de p38 MAPK pode reduzir a resposta imune inata e, consequentemente, inibir a HI após a arterialização do EVS. 12,13 Com base nesses estudos em HI, formulamos a hipótese de que a atorvastatina poderia reduzir o acúmulo de CMLVs para inibir HI por meio da supressão da via p38 MAPK.…”
Section: Introductionunclassified